Effect of iridium doping on electronic structure and optical properties of m-BiVO4 photocatalytic materials: a first principles study. (4th March 2022) - Liu, Jianbo; Liu, Fenjun; Bai, Haiqiang; Zhuang, Weijun; Xu, Yunhua
Abstract : To improve the photocatalytic performance of m -BiVO4 materials, iridium doping in m -BiVO4 (0 0 1) crystal was studied using CAmbridge Serial Total Energy Package calculation module based on density functional theory. By calculating the formation energy of Ir doped in m -BiVO4 crystal at different doping positions and different content, model of Bi atom substituted by 6.25% Ir with the Ef of 0.887 eV was selected as a research object. The splitting and transferring of Ir 5 d orbit from high localised state to two peaks of state density distributed on sides of conduction band (CB) and valence band (VB) are benefitted for electron transfer and charges redistribution. The band gap value decreased from 2.218 to 1.203 eV after doping Ir element and three hybrid energy bands arised between the VB and CB. The energy range of VB and CB is −5.68∼0.40 eV and 1.90∼7.42 eV, which is mainly the contribution of interaction between O 2 p orbit and V 3 d orbit, V 3 d orbit and Bi 6 p orbit, respectively. The iridium doping introduced the impurity levels near the Fermi energy level ( EF ), narrowed the band gap and reduced the transition energy barrier of photo-generated electrons and made the electrons transition process more easily. GRAPHICAL ABSTRACT: UF0001